Environmental Taxation Through a Bibliometric Lens: Finding Leading Voices, Trends, and Gaps - Apriantoro, Muhamad Subhi; Maulana, Ilham (International Journal of Energy Economics and Policy, 2025)
This paper conducts a bibliometric analysis of environmental taxation to assess its role in sustainable development amidst escalating environmental and climate challenges. The study is motivated by the critical need for fiscal mechanisms that generate revenue and promote sustainable practices. Analyzing publication patterns, citations, and thematic evolutions provides a comprehensive review of the academic discourse on environmental taxation, identifying leading contributors, prevalent trends, and notable gaps in the field. Findings indicate a complex array of themes, notably the economic impacts of environmental taxes, their integration with broader fiscal reforms, and their influence on eco-friendly innovations. The research highlights varied implementation strategies and effectiveness across jurisdictions and an increasing interest in linking environmental taxes with renewable energy and public health policies. However, a significant gap exists in empirical research on the long-term effects of these taxes on economic and environmental outcomes, suggesting a need for deeper investigation to inform policy development and refinement. This gap points to future research directions, emphasizing a more integrated and comprehensive approach to environmental fiscal policies globally.